RETRACTED: Silencing circular RNA VANGL1 inhibits progression of bladder cancer by regulating miR‐1184/IGFBP2 axis - Dengke Yang; Haining Qian; Zhen Fang; An Xu; Shutian Zhao; Bingyan Liu; Dong Li (Cancer Medicine)
Abstract Circular RNA VANGL1 (circVANGL1) is generated from two exons of the Van Gogh‐like 1 (VANGL1) gene and serves as a tumor promoter by sponging certain microRNAs (miRNAs). However, the role of circVANGL1 in bladder cancer (BC) is still unclear. So, in order to investigate the role of circVANGL1 in BC, quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR) was employed to evaluate the circVANGL1 expression in tumor tissues from BC patients and in BC cell lines. Small interfering RNA against circVANGL1 was constructed and stably transfected into human bladder epithelium immortalized cells (SV‐HUC). Cell invasion and migration were detected in Transwell chambers, cell proliferation was determined by CCK8 assays, and tumorigenesis in nude mice was examined to assess the effect of circVANGL1 in BC. Subcellular localization of circVANGL1 was confirmed by fluorescence in situ hybridization. The interactive relationships among circVANGL1, miRNA, and relative proteins were confirmed by luciferase reporter assays. The results showed that circVANGL1 was upregulated in both BC tissues and cell lines. Silencing the expression of circVANGL1 suppressed cell invasion, migration, and proliferation during in vitro experiments. Mechanistically, we demonstrated that circVANGL1 upregulated the expression of miR‐1184 target gene insulin‐like growth factor‐binding protein 2 (IGFBP2) by sponging miR‐1184, which promoted the aggressive biological behaviors of BC. Taken together, our results indicate that circVANGL1 acts as a tumor promoter through the novel circVANGL1/miR‐1184/IGFBP2 axis. Hopefully, our study will provide new ideas for the clinical treatment of BC.